Bone remodeling in the longest living rodent, the naked mole-rat: Interelement variation and the effects of reproduction - Montoya-Sanhueza, Germán; Bennett, Nigel C; Oosthuizen, Maria K; Dengler-Crish, Christine M; Chinsamy, Anusuya (Journal of anatomy, 2021)
The pattern of bone remodeling of one of the most peculiar mammals in the world, the naked mole-rat (NMR), was assessed. NMRs are known for their long lifespans among rodents and for having low metabolic rates. We assessed long-term in vivo bone labeling of subordinate individuals, as well as the patterns of bone resorption and bone remodeling in a large sample including reproductive and non-reproductive individuals (n = 70). Over 268 undecalcified thin cross-sections from the midshaft of humerus, ulna, femur and tibia were analyzed with confocal fluorescence and polarized light microscopy. Fluorochrome analysis revealed low osteogenesis, scarce bone resorption and infrequent formation of secondary osteons (Haversian systems) (i.e., slow bone turnover), thus most likely reflecting the low metabolic rates of this species. Secondary osteons occurred regardless of reproductive status. However, considerable differences in the degree of bone remodeling were found between breeders and non-breeders. Pre-reproductive stages (subordinates) exhibited quite stable skeletal homeostasis and bone structure, although the attainment of sexual maturity and beginning of reproductive cycles in female breeders triggered a series of anabolic and catabolic processes that up-regulate bone turnover, most likely associated with the increased metabolic rates of reproduction. Furthermore, bone remodeling was more frequently found in stylopodial elements compared to zeugopodial elements. Despite the limited bone remodeling observed in NMRs, the variation in the pattern of skeletal homeostasis (interelement variation) reported here represents an important aspect to understand the skeletal dynamics of a small mammal with low metabolic rates. Given the relevance of the remodeling process among mammals, this study also permitted the comparison of such process with the well-documented histomorphology of extinct therapsids (i.e., mammalian precursors), thus evidencing that bone remodeling and its endocortical compartmentalization represent ancestral features among the lineage that gave rise to mammals. It is concluded that other factors associated with development (and not uniquely related to biomechanical loading) can also have an important role in the development of bone remodeling.
Keywords: Secondary reconstruction; rozmnožování; Haversian systems; Mole Rats; mikroftalmičtí podzemní hlodavci; zvířata; remodelace kosti; ženské pohlaví; Bone resorption; Female; mužské pohlaví; Heterocephalus glaber; Male; Animals; Female breeder; Secondary osteons; Reproduction; Bone Remodeling